Biot-Savart Props Based on Arduino Uno For Measuring Magnetic Fields on Wire and Solenoids - Utari, Nupita; Hamdani, Dedy; Gunawan, Bodi (Universitas Syiah Kuala, 2025)
The purpose of this study is to develop an Arduino Uno-based prop to visualize and measure the magnetic field around straight wires and solenoids according to the Biot-Savart law. This tool is designed using HMC5883L sensors that are able to detect magnetic fields in three axes with high accuracy. This research applies the Research and Development (RD) method with the ADDIE model. There are five stages of this research process, namely analysis, design, development, implementation and evaluation. The results of the validation conducted by media experts show that this teaching tool is very suitable for use, with an average score of 88.18%. The application of teaching aids to grade XII students of MIPA 1 SMAN 04 South Bengkulu improved students' science process skills with an average of 90.23% in the